Instantaneous speed ratio of traffic flowing through a merging area at kilometer 31.6 on the highway from shah alam to kuala lumpur - Basri N.S.H.; Mohamed N.A.; Adnan M.A.; Mohamed N.F.; Zainuddin N.H. (Universiti Putra Malaysia Press, 2024)
Indexed by Scopus